God as Sound-Conciousness - Irene Ludji (Asosiasi Teolog Indonesia, 2014)
This paper describes the concept of sacred sound in Hinduism as a way for the Hindu to approach and to know the Christian God. Different from Christians who are known as the people of the book, Hindu people are known as the people of the sound. The vocalic syllable Om or Aum and the repeating/chanting of the sacred sound in Hindu worship give a unique room to a new and different way of knowing God. God is no longer perceivable as the powerful figure in the book but as consciousness. The word “consciousness” in this paper refers to the ability of believers to be mindful and responsive to God. This paper will also describe the concept of sonic theology as a different way to perceive God in Hinduism and relate it to the practice of Yoga that is widely practiced in the modern world today.